Redistribution and Unemployment Insurance - Antoine Ferey (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2022)
This paper analyzes the interactions between redistribution and unemployment insurance policies and their implications for the optimal design of tax-benefit systems. In a setting where individuals with different earnings abilities are exposed to unemployment risk on the labor market, I characterize the optimal income tax schedule and the optimal unemployment benefit schedule in terms of empirically estimable sufficient statistics. I provide a Pareto-efficiency condition for tax-benefit systems that implies a tight link between optimal redistribution and optimal unemployment insurance: the steeper the profile of income taxes is, the flatter the profile of unemployment benefits should be, and vice versa. Optimal replacement rates are therefore monotonically decreasing with earnings, from 1 at the bottom of the earnings distribution to 0 at the top, and redistribution through unemployment benefits is efficient. Empirical applications show that these interactions between redistribution and unemployment insurance have important quantitative implications.
Keywords: 330